The Analysis of Shallot Farming Income in Pabedilan District, Cirebon Regency - Ricardo, Yogi; Francisca, Camelya; Amelia, Ela; Dwirayani, Dina (Jurnal Agrosci, 2025)
Background. One of the leading commodities in Cirebon Regency is shallots. Differences in planting seasons can affect farmers' incomes. Aims. The purpose of this study is to analyze the income and feasibility of shallot farming in the dry season and rainy season. Methods. This research was conducted in Pabedilan District, one of the largest shallot production centers in Cirebon Regency. Data collection in this study was conducted through surveys and interviews using structured questionnaires with 30 respondents, comprising the same group of shallot farmers in both the dry and rainy seasons. The analysis methods used in this study include calculating income, revenue, r/c ratio, b/c ratio, and performing a t-test to compare income between the rainy season and the dry season. Result. The results of this study show that the average total cost of the dry season is Rp. 138,829,827.74, the rainy season is Rp. 152,388,777.74, and the income of farming in the dry season is Rp. 74,408,560.75, and the rainy season amounted to Rp. 250,425,154.12, the dry season revenue was 213,238,388.49 and the rainy season was 402,813,931.86, the dry season r/c ratio was 1.53, the rainy season was 2.64, the dry season b/c ratio was 0.53, the rainy season was 1.64, the statistical test showed a significant difference between the income of the two seasons with a significance value of 0.027. Conclusion. This finding indicates that shallot farming in Pabedilan District is feasible in both seasons; however, it is more profitable when carried out during the rainy season.